In silico design of dual-doped nitrogenated graphene (C2N) employed in electrocatalytic reduction of carbon monoxide to ethylene. Issue 9 (4th February 2022) - Wang, Honglei; Ren, Guoqing; Zhao, Yanliang; Sun, Lanju; Sun, Jikai; Yang, Li; Yu, Tie; Deng, Weiqiao; Sun, Lei
Abstract : Electrocatalytic reduction of carbon monoxide (CO) to valuable multi-carbon chemicals is among the most promising methods to ensure a sustainable carbon cycle. Abstract : The electrocatalytic reduction of carbon monoxide (CO) to valuable multi-carbon chemicals is among the most promising methods to ensure a sustainable carbon cycle. Many catalysts have been developed to achieve efficient conversion; however, research efforts on CO reduction have rarely focused on metal-free catalysts despite them being naturally abundant, non-toxic, environmentally friendly, and possessing a controllable composition. In this paper, a theoretical design of heteroatom-doped (B, P, and S atoms) nitrogenated graphene (C2 N)-based electrocatalysts with dual-site synergism is reported and discussed. The average CO adsorption energy and ethylene desorption energy are used for the primary screening of various dual-atom combinations, while the stability of the catalysts is used for subsequent screening. It is found that B&P/C2 N is suitable for use as an electrocatalyst. In addition, the hydrogenation of the *COCO intermediate with a free-energy increase of 0.44 eV is reported to be the rate-determining step, and the product (C2 H4 ) can easily escape from it. This work will assist in the future design of more efficient metal-free catalysts for facilitating the sustainable synthesis of C2 H4 .